Remote sensing reveals scale‐specific effects of forage crop mowing and landscape structure on a declining farmland bird - Andreatta, D.; Bazzi, G.; Nardelli, R.; Siddi, L.; Cecere, J. G.; Chamberlain, D.; Morganti, M.; Rubolini, D.; Assandri, G. (Journal of Applied Ecology, 2025)
The effectiveness of agri-environment schemes (AESs), the largest conservation-related expenditure for farmland biodiversity conservation within the European Union, is often compromised by a limited spatial scale of implementation. We focused on multiannual forage crops, a surrogate habitat for grassland birds, to assess the scale-dependent effects of mowing timing and frequency on the local population size of an iconic species, the skylark (Alauda arvensis). While there is much evidence for a negative impact of in-field mowing activities on grassland birds, whether such effects occur also at broader spatial scales is largely unknown. We surveyed breeding skylarks in the Po Plain (northern Italy) to determine (1) the association between landscape composition/configuration and abundance and (2) how abundance is affected by forage crop mowing timing and frequency. We addressed both questions through scale optimisation, identifying the most influential spatial scales for each covariate. Forage crop mowing timing was assessed through a novel remote sensing algorithm based on high-resolution Sentinel-2 satellite images. We observed a strong scale dependence on the importance of different habitats in determining skylark abundance. Abundance increased with an increasing cover of forage crops locally (200 m) and of winter crops at a landscape scale (2600 m), suggesting that the species is favoured by heterogeneous agroecosystems. Locally (150–350 m), skylarks were more abundant when crops were aggregated, being negatively impacted by crop fragmentation caused by urbanization and by seminatural habitats. At the landscape scale (1150 m), the timing of mowing was consistent across years, with early-mown areas supporting fewer skylarks. This is probably because, over longer temporal scales, early-mown forage patches have limited or null productivity, eventually limiting local population size. Synthesis and applications. We provide a new perspective on the overarching influence of spatial scale in driving the abundance of a ...